Synergistic effect of rice husk ash and ceramic powder on mechanical properties of ultra-high-performance concrete - Trinh, Hoang; Fernando, P.H.; Tran, Tung; Pham, Thong (2024)
This research examines the synergistic impacts of incorporating rice husk ash (RHA) and ceramic powder (CP) in ultra-high-performance concrete (UHPC). Four alternatives of UHPCs with different contents of RHA and CP were investigated. Specifically, the first two batches substituted silica fume (SF) with RHA at levels of 5 %, 10 %, and 15 %, whereas 10 %, 15 %, and 20 % RHA was used to replace cement in the third batch. The last batch, on the other hand, was designed to examine the synergistic effect of a fixed 5 % RHA and CP replacement proportions of 10 %, 15 %, and 20 %. Mechanical properties (i.e. compressive/flexural resistance and damping ratio), economic efficiency, and environmental impacts of the newly designed mixtures were determined. Compared to the reference mix, all mixtures experienced declined workability. While using RHA to replace SF exhibited either comparable or enhanced compressive and bending capacities, mixes with cement substitution had lower compressive strengths but higher flexural strengths. Regardless of substituting cement or SF, incorporating RHA consistently augmented the damping performance of the UHPC blends. The inclusion of both RHA and CP resulted in up to 17.2 % higher compressive strength, 47.9–59.1 % higher flexural strength, and 68 % higher damping ratio compared to the control mix, highlighting their favourable synergistic effects for developing high-performance and eco-friendly UHPC mixtures. The developed mixtures also demonstrated improvements of up to 40 % in cost-efficiency and reductions of up to 10.1 % in embodied carbon emissions (38 % carbon index).